2016
DOI: 10.1002/pat.3798
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property evaluation of glass–jute fiber reinforced polymer composites

Abstract: The natural fibers such as jute, coir, hemp, sisal etc. are randomly used as reinforcements for composite materials because of its various advantages such as low cost, low densities, low energy consumption over conventional fibers. In addition, they are renewable as well as biodegradable, and indeed wide varieties of fibers are locally available. In this study, glass–jute fiber reinforced polymer composite is fabricated, and the mechanical properties such as tensile, flexural and impact behavior are investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Isotropic material properties were assigned to the plies and error between simulation and experimental values was found to be more than 10%. This study proved that while working with woven reinforcements and jute natural fiber there exists a possibility of error up to 15-20% [6].…”
Section: Introductionmentioning
confidence: 54%
“…Isotropic material properties were assigned to the plies and error between simulation and experimental values was found to be more than 10%. This study proved that while working with woven reinforcements and jute natural fiber there exists a possibility of error up to 15-20% [6].…”
Section: Introductionmentioning
confidence: 54%
“…In another study, Rafiquzzaman et al. [13] fabricated jute, glass and jute/glass hybrid composites and studied their mechanical performances. Results showed that jute (tensile strength: 40 MPa, impact strength: 179 J/m 2 ) and glass fibre reinforced composite samples (tensile strength: 86 MPa, impact strength: 235 J/m 2 ) exhibited significant differences in tensile and impact strength [13].…”
Section: Introductionmentioning
confidence: 99%
“…In numerical analysis, the individual composite plates were joined together to represent the whole model and an error of nearly 20% was observed between experimental and numerical model. They alluded that this might be due to the presence of voided content in the experimental model as a result of awed fabrication method [12].…”
Section: Introductionmentioning
confidence: 99%
“…The natural jute bers based composites are seen extensively in many automobiles parts, furniture equipment, storage of agricultural products, sports goods, and many chemical products [11]. There are plethora of experimental [12][13][14][15][16][17][18] and a few numerical techniques [19][20][21] for the mechanical characterization of Natural Fiber-Reinforced Composite (NFRPC) materials or only Natural Fiber Composites (NFC). These numerical techniques can successfully predict the mechanical properties of NFC and different synthetic bers reinforced composite within an acceptable error range [19 − 20] , [22].…”
Section: Introductionmentioning
confidence: 99%